Is peer review useful in assessing research proposals in Indigenous health? A case study - Baum Fran; Street Jackie; Anderson Ian PS (BMC, 2009)
Abstract Background There has been considerable examination and critique of traditional (academic) peer review processes in quality assessment of grant applications. At the same time, the use of traditional research processes in Indigenous research has been questioned. Many grant funding organisations have changed the composition of their peer review panels to reflect these concerns but the question remains do these reforms go far enough? In this project we asked people working in areas associated with Aboriginal health research in a number of capacities, their views on the use of peer review in assessing Indigenous research proposals. Methods In semi-structured interviews we asked 18 individuals associated with an Australian Indigenous research funding organisation to reflect on their experience with peer review in quality assessment of grant applications. We also invited input from a steering group drawn from a variety of organisations involved in Aboriginal research throughout Australia and directly consulted with three Aboriginal-controlled health organisations. Results There was consensus amongst all participants that traditional academic peer review is inappropriate for quality assessment in Indigenous research. Many expressed the view that using a competitive grant review system in Aboriginal health was counterintuitive, since good research transfer is based on effective collaboration. The consensus within the group favoured a system which built research in a collaborative manner incorporating a variety of different stakeholders in the process. In this system, one-off peer review was still seen as valuable in the form of a "critical friend" who provided advice as to how to improve the research proposal. Conclusion Peer review in the traditional mould should be recognised as inappropriate in Aboriginal research. Building research projects relevant to policy and practice in Indigenous health may require a shift to a new way of selecting, funding and conducting research.